Anthocyanin content, phenolic content, antioxidant activity and yield in indigenous rice as affected by different fertilizers (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Prajuntasan R, Ratananikom K, Payoungkiattikun W. 2022. Anthocyanin content, phenolic content, antioxidant activity and yield in indigenous rice as affected by different fertilizers. Biodiversitas 23: 4195-4201. This study was to evaluate the effects of fertilizer management methods (organic and inorganic) on total anthocyanin content (TAC), total phenolic content (TPC), antioxidant activity, and yield in eight local rice varieties. A 2×8 factorial experiment in a randomized complete block design with three replications was setup on a farmer’s farm. Organic fertilizer management increased TAC, TPC and antioxidant activity, but significant increases were found for TAC,and antioxidant activity. The highest TAC was found in Luem Puew, and Kum Puen Baan had the highest TPC. The highest TAC and TPCvarietiesdid not necessarily havethe highest antioxidant activity. Sung Yod, Chaow Daeng, Kum Ka Dum and Kum Puen Baan were the highest for this parameter. Luem Puew + organic was the treatment combined with the highest TAC. Still, the result found the highest antioxidant activities in several treatment combinations associated with most local rice varieties except Nang Nuan and Mali Nga Chang.